Evidence of counter-gradient growth in western pond turtles (Actinemys marmorata) across thermal gradients - Snover, Melissa L.; Adams, Michael J.; Ashton, Donald T.; Bettaso, Jamie B.; Welsh Jr, Hartwell H. (Freshwater biology, 2015)
Summary Counter‐gradient growth, where growth per unit temperature increases as temperature decreases, can reduce the variation in ectothermic growth rates across environmental gradients. Understanding how ectothermic species respond to changing temperatures is essential to their conservation and management due to human‐altered habitats and changing climates. Here, we use two contrasting populations of western pond turtles (Actinemys marmorata) to model the effect of artificial and variable temperature regimes on growth and age at reproductive maturity. The two populations occur on forks of the Trinity River in northern California, U.S.A. The South Fork Trinity River (South Fork) is unregulated, while the main stem of the Trinity River (Main Stem) is dammed and has peak seasonal temperatures that are approximately 10 °C colder than the South Fork. Consistent with other studies, we found reduced annual growth rates for turtles in the colder Main Stem compared to the warmer South Fork. The South Fork population matured approximately 9 year earlier, on average, and at a larger body size than the Main Stem population. When we normalised growth rates for the thermal opportunity for growth using water‐growing degree‐days (GDD), we found the reverse for growth rates and age at reproductive maturity. Main Stem turtles grew approximately twice as fast as South Fork turtles per GDD. Main Stem turtles also required approximately 50% fewer GDD to reach their smaller size at reproductive maturity compared to the larger South Fork turtles. We found we could accurately hindcast growth rates based on water temperatures estimated from the total volume of discharge from the dam into the Main Stem, providing a management tool for predicting the impacts of the dam on turtle growth rates. Given the importance of size and age at reproductive maturity to population dynamics, this information on counter‐gradient growth will improve our ability to understand and predict the consequences of dam operations for downstream turtle populations.